A Case Series CT AND MR IMAGING OF BENIGN AND MALIGNANT MENINGIOMA: HOW TO DIFFERENTIATE? - Faturrohmaniah, Ari; Yueniwati, Yuyun (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
Introduction: Typical meningiomas are benign tumors, while atypical and anaplastic ones tend to be malignant. Typical meningiomas are mostly detected in women who are 40 years of age, presenting with minimal peritumoral edema and homogeneous enhancement. Atypical meningiomas increased in men who are more than 60 years of age, exhibiting severe peritumoral edema, heterogeneous enhancement, large sizes, and low ADC values. Most anaplastic meningioma cases occur, but rarely, in children, which are highly invasive, growing rapidly, destroying calvarial bone, and have a giant intracranial tumor that invades the extracranial soft tissue and forms a cutaneous mass. Case Presentation: A 37-, 39-, and 15-year-old female patients were presented. There was blurred vision in the right eye, difficulties in communicating, and headaches for 2 years in the first case; vertigo and headaches for a year in the second case; and headaches, vertigo, and blurred vision for 2 years in the last case, growing more severe in the recent month. Based on MRI, the first patient had an extra-axial homogeneous mass with minimal peritumoral edema, homogeneous enhancement consistent with the appearance of typical falx meningioma; the second case had an extra-axial heterogeneous mass with necrotic component, severe peritumoral edema, and heterogeneous enhancement on the right temporoparietal region consistent with the appearance atypical meningioma; the last case had an extra-axial heterogeneous giant mass with necrotic component, severe peritumoral edema, and heterogeneous enhancement on right frontal region based on CT and MRI. CTA showed increased internal vascularity inside and adjacent to the lesion, and the bone window showed erosion and thinning of the calvarial bone, consistent with the appearance of anaplastic falx meningioma of the malignant characteristics. Conclusion: Age, gender, tumor size, peritumoral edema severity, degree of enhancement, restriction on DWI, vascularity, and hyperostosis or erosion of bone can distinguish between benign and malignant meningioma. Keywords: typical meningioma, atypical meningioma, anaplastic meningioma.